ANALISIS KEBIJAKAN PEMBERDAYAAN PELAKU UMKM DI KABUPATEN KARO PROVINSI SUMATERA UTARA - Esma Dewi Br. Surbakti; Matius Bangun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This study aims at studying the activities carried out by the Karo Regency Government in order to empower micro business actors in Berastagi District and analyzing the income of micro business actors from the empowerment efforts carried out by the Karo Regency government. This study is located in Berastagi Subdistrict on culinary businesses, micro culinary businesses, micro-fruit and vegetable businesses and flower-flower micro businesses. The method used is descriptive qualitative data collection based on interviews and observations for primary data, while literature studies, social media and documentation. Data analysis is a policy analysis on the empowerment of micro businesses regarding the preparation, partiality, protection and income analysis of micro-entrepreneurs . The conclusion of this study is that the average income of Umkl is Rp. 3,275,050, - according to the criteria issued by BPS (2011) is classified as high. Umbs income Rp. 2,556,700, - increased to Rp. 3,402,400, - or classified as high. Likewise with the income of the micro interest (Umbg) business of Rp. 2,350,760, - classified as moderate income.The average income of Umkl through Empowerment has increased from Rp. 3,617,680, - classified as Very High, Umbs Income is Rp. 3,402,400, - High. 3. Likewise with the Umbg to Rp. 2,951,100, - or classified as high income. In terms of percentage, the highest increase in income occurred in fruit and vegetable business actors, amounting to 33.07%, followed by income of interest micro-entrepreneurs by 25.54%, while the smallest occurred in culinary micro business actors at 10.46%. Based on the UMK Karo Regency of Rp. 3,077,354.39, it can be seen that the Culinary Micro Business Income (UMKl) is Rp. 3,617,680, -. Fruit and vegetable micro business actors (Umbs) Rp. 3,402,400, - Interest income micro business (Umbg), interest business actor (UMBg) Rp. 2,951,100, -. Based on the UMK, the Umkl and Umbs Income is above the UMK while the Umbg Income is closer to the UMK.